The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.15251/jor.2020.161.11
|View full text |Cite
|
Sign up to set email alerts
|

SYNTHESIS, STRUCTURAL AND OPTICAL PROPERTIES OF Zn-SUBSTITUTED Co W-FERRITES BY COPRECIPITATION METHOD

Abstract: A series W-type BaMe2Fe16O27 ferrites withcomposition BaZnxCo1-xFe16O27(x ═ 0.0, 0.1, 0.2, 0.3, 0.4 &0.5) were manufactured by co-precipitation method sintering at 1100°C for 8 h. XRD, FTIR, SEM, UV-vis and I-V techniques were applied to investigate structural, optical, morphological and electrical properties respectively. Crystallite size was observed in the range of (37.58 nm- 54.75 nm) revealed by XRD and was confirmed by SEM analysis. IR exposed the existence of metal oxides (M -O). Optical band gap wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…6 that the optical bandgap is drastically decreased by the incorporation of a small amount of Ni 2+ at values of x up to x = 0.2, however, a further increase in the Ni 2+ concentration does not have a significant effect on the bandgap values. [26,31,[40][41][42][43][44] These results suggest that the synthesized samples are potential candidates for use in various optoelectronic applications.…”
Section: Uv-vis Analysismentioning
confidence: 99%
“…6 that the optical bandgap is drastically decreased by the incorporation of a small amount of Ni 2+ at values of x up to x = 0.2, however, a further increase in the Ni 2+ concentration does not have a significant effect on the bandgap values. [26,31,[40][41][42][43][44] These results suggest that the synthesized samples are potential candidates for use in various optoelectronic applications.…”
Section: Uv-vis Analysismentioning
confidence: 99%
“…It was observed that the dislocation density was increased with the addition of Zn from 4.06 × 10 -4 nm -2 to 6.46 × 10 -4 nm -2 , as presented in Table 1. The Braggs equation was used to determine the interplanar distance (d), that is given below [10][11][12][13];…”
Section: X-ray Diffraction Analysismentioning
confidence: 99%
“…For the synthesis of spinel structure materials, different synthesized techniques were used, including the solgel auto combustion technique [26,27], solvothermal process [28], and coprecipitation route [29][30][31]. The auto combustion (sol-gel) process is commonly used because of its easy synthesis and economical fabrication [25].…”
Section: Introductionmentioning
confidence: 99%